Corn gluten hydrolysis by alcalase : effects of process parameters on hydrolysis, solubilization and enzyme inactivation - Kilic Apar, Dilek (Array, 2008)
Summary: The aim of this study was to investigate the influences of substrate concentration, enzyme concentration, temperature and pH on hydrolysis and solubilization of corn gluten as well as enzyme stability. The corn gluten was hydrolyzed by Alcalase enzyme (a bacterial protease produced by a selected strain of Bacillus licheniformis) that was chosen among five commercial enzymes examined.The optimum process conditions for hydrolysis and solubilization were obtained as 30 g L–1 substrate mass concentration, 2.5 mL L–1 enzyme concentration, 55 °C and pH 8. Under these conditions, the values of degree of hydrolysis and solubilization were found as 28.4 % and 85.3 % respectively; and enzyme lost its activity by approximatively 74 % at the end of 120 min processing time.Modelling studies were performed to determine the kinetics of hydrolysis, solubilization and enzyme inactivation. The relationship between hydrolysis and solubilization was found linear for all experimental conditions examined.The inactivation energy of Alcalase at the temperature range of 40–55 °C was determined to be 67.86 kJ mol–1